2019
DOI: 10.1002/aorn.12662
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Perioperative Hair Removal Practices

Abstract: The standard of practice for perioperative hair removal is largely based on research that is outdated and underpowered. Although there is evidence to support the practice of clipping instead of shaving, current recommendations are to remove hair only when absolutely necessary. Human hair is bacteria‐laden and challenging to disinfect, and clipping can be a safe method of hair removal that does not damage the skin. This article considers the removal of hair at the incision site with clippers, either before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A recent study demonstrated that the use of the vacuum suction device resulted in a significant reduction in the total time needed to cut and clean the residual hair that contaminates the operating field compared to standard practice (eliminating the need to physically remove the scattered hair, which can harbor a significant microbial load, within the surgical field) 19 .…”
Section: Objective Results Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that the use of the vacuum suction device resulted in a significant reduction in the total time needed to cut and clean the residual hair that contaminates the operating field compared to standard practice (eliminating the need to physically remove the scattered hair, which can harbor a significant microbial load, within the surgical field) 19 .…”
Section: Objective Results Conclusionmentioning
confidence: 99%
“…Innovative haircut and vacuum technologies can help remove hair more safely by eliminating the dispersion of hair fibers around the incision site, mitigating the risk of hair contaminating the surgical incision 19 .…”
Section: Objective Results Conclusionmentioning
confidence: 99%
“…27 Additionally, some medical organizations have called for clipping hair only when necessary. 28 However, these improvements would be more effective if all hospitals and doctors followed more rigorous modesty protocols. For instance, providing improved gowns and surgical undergarments to patients is pointless if medical staff remove them without the patient's knowledge, such as in the case of John.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…According to a review from Edmiston et al, hair removal is considered as preoperative and perioperative clipping without damaging the skin. In this way, bacterial contamination by existing hair and insufficient disinfection may be kept to a minimum [ 32 ].…”
Section: Avoiding Surgical Site Infectionsmentioning
confidence: 99%